2017
DOI: 10.1002/mc.22708
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase 5 (NOX5)—induced reactive oxygen signaling modulates normoxic HIF‐1α and p27Kip1 expression in malignant melanoma and other human tumors

Abstract: NADPH oxidase 5 (NOX5) generated reactive oxygen species (ROS) have been implicated in signaling cascades that regulate cancer cell proliferation. To evaluate and validate NOX5 expression in human tumors, we screened a broad range of tissue microarrays (TMAs), and report substantial overexpression of NOX5 in malignant melanoma and cancers of the prostate, breast, and ovary. In human UACC-257 melanoma cells that possesses high levels of functional endogenous NOX5, overexpression of NOX5 resulted in enhanced cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 78 publications
1
26
0
1
Order By: Relevance
“…HIF1 also responds to nonhypoxic stimuli, including ROS, which regulate HIF1a stability and transcriptional activity (42). A very recent report demonstrates that HIF1a expression is upregulated in prostate cancer cells with induced NOX5 overexpression (43).…”
Section: A Bidirectional Crosstalk Is Observed Between Prostate Cancementioning
confidence: 99%
“…HIF1 also responds to nonhypoxic stimuli, including ROS, which regulate HIF1a stability and transcriptional activity (42). A very recent report demonstrates that HIF1a expression is upregulated in prostate cancer cells with induced NOX5 overexpression (43).…”
Section: A Bidirectional Crosstalk Is Observed Between Prostate Cancementioning
confidence: 99%
“…Overexpression of Noxs and uncontrolled redox‐dependent cell proliferation have been demonstrated in various cancers (Gào & Schöttker, ; Roy et al., ). NOX5 expression and activity are increased in gastric cancer, malignant melanoma, breast cancer, prostate cancer and oesophageal cancer (Antony et al., ; Dho et al., ; Gào & Schöttker, ; Kalatskaya, ; Roy et al., ). Increased Nox activity and dysregulated production of ROS cause tissue injury, DNA damage and uncontrolled cell proliferation that are already evident in pre‐malignant conditions, especially Barrett's oesophagitis (Kalatskaya, ).…”
Section: Pathophysiology Of Nox5mentioning
confidence: 99%
“…Increased Nox activity and dysregulated production of ROS cause tissue injury, DNA damage and uncontrolled cell proliferation that are already evident in pre‐malignant conditions, especially Barrett's oesophagitis (Kalatskaya, ). Pathways implicated in these NOX5–ROS‐dependent processes include signalling molecules (MAP kinases, PI3K, PKC and p27Kip1), transcription factors (APE1/Ref‐1, hypoxia‐inducible factor‐1α, AP‐1, Nrf2, nuclear factor‐κB, p53, FOXO, STAT5A and β‐catenin) (Antony et al., ; Dho et al., ; Roy et al., ) and adaptor proteins (Ruk/CIN 85) (Bazalii, Horak, Pasi chn yk, Komisarenko, & Drobot, ).…”
Section: Pathophysiology Of Nox5mentioning
confidence: 99%
“…NOX5-derived ROS is suggested to promote proliferation of prostate cancer cell by modulating the activity and expression of protein kinase C zeta and c-Jun N-terminal kinase, 9 and enhance cell growth of melanoma through activation of hypoxia-inducible factor 1-alpha signaling pathways. 42 But, so far, little is known about the function of NOX5 in GC. In the present study, we found NOX5 mRNA expression was modestly lower in GC tissues compared with that in normal stomach tissues.…”
Section: Discussionmentioning
confidence: 99%